Recessive myotonia congenita caused by a homozygous splice site variant in CLCN1 gene: a case report - Peter Sparber; Margarita Sharova; Alexandra Filatova; Olga Shchagina; Evgeniya Ivanova; Elena Dadali; Mikhail Skoblov (BMC, 2020)
Abstract Background Myotonia congenita is a rare neuromuscular disease, which is characterized by a delay in muscle relaxation after evoked or voluntary contraction. Myotonia congenita can be inherited in a dominant (Thomsen disease) and recessive form (Becker disease) and both are caused by pathogenic variants in the CLCN1 gene. Noncanonical splice site variants are often classified as variants of uncertain significance, due to insufficient accuracy of splice-predicting tools. Functional analysis using minigene plasmids is widely used in such cases. Moreover, functional analysis is very useful in investigation of the disease pathogenesis, which is necessary for development of future therapeutic approaches. To our knowledge only one noncanonical splice site variant in the CLCN1 gene was functionally characterized to date. We further contribute to this field by evaluation the molecular mechanism of splicing alteration caused by the c.1582 + 5G > A in a homozygous state. Case presentation We report a clinical case of an affected 6-y.o boy with athletic appearance due to muscle hypertrophy, calf muscle stiffness, cramping and various myotonic signs in a consanguineous family with no history of neuromuscular disorders. The neurological examination showed percussion-activated myotonia in the hands and legs. Plasma creatine kinase enzyme and transaminases levels were normal. Electromyography at the time of examination shows myotonic runs in the upper and lower extremities. Conclusions Functional analysis of the variant in a minigene system showed alteration of splicing leading to loss of function, thereby confirming that the variant is pathogenic.